Who should make corporate law? EC legislation versus regulatory competition - Armour, J (Oxford University Press, 2005)
The beginning of the twenty-first century has brought with it an extraordinary set of stimuli for company law reform in the EU. A series of well-publicised recent scandals on both sides of the Atlantic have shaken faith in existing company law frameworks. Contemporaneously, in the wake of the ECJ’s decisions in the Centros line of cases,¹ EU Member States are, for the first time, seemingly on the threshold of regulatory competition over the content of company law. The result has been protracted debates about the optimal ‘model’ for company law, informing an unprecedented volume of reform activity, both at EU and Member State level. A logically prior question concerns the allocation of jurisdiction to make the relevant reforms across the vertical, or ‘federal’, dimension—as between the EU and Member States.² This question is the subject of the current paper